GREEN BUILDING IMPLEMENTATION STUDY BASED ON EFICIENCY ENERGI in RUMAH JOGLO as DEVELOPMENT OF TEACHING MATERIALS COURSE PROGRAM AND PLANNING APPLICATION - Andini Dwi Prihatini; AG Thamrin; Chundakus Habsya (Universitas Sebelas Maret, 2017)
Abstract: This research bolawins was purposed to knowing (1) the implementation of greenbuilding on aspect natural lighting in Rumah Joglo terms of SNI 03-6197-2000; (2) theimplementation of green building on aspect natural ventilation in Rumah Joglo termsSNI 03-6572-2001; (3) the implementation of green building in Rumah Joglo fordevelopment of teaching materials course Program and Planning Application in PTBFKIP UNS. This research was conducted by measuring the natural lighting, airvelocity, relative huminidity, and air temperature in each room in the Rumah Joglo aswell as the occupants questionnaire provide. The subjects were five Rumah Joglo. Theresult showed that 89,74% of natural lighting in the research subjects does not meet therequirements of SNI 03-6197-2000, 82,25% of air velocity does not meet therequirements of SNI 03-6572-2001, for relative huminidity and air temperature in theobject of study does not meet the requirements of SNI 03-6572-2001. The result of thisresearch can be use for development of teaching materials course Program andPlanning Application in PTB UNS.Keyword: Joglo, Natural Lighting, Natural Ventilation